Advanced radiotherapy techniques for breast cancer to minimize cardiovascular risk. (May 2014) - Mackenzie, Penny; Fyles, Anthony; Wang, Wei; Chung, Caroline
SUMMARY : Radiotherapy plays an integral role in the management of breast cancer and has been demonstrated to reduce the risk of recurrence and improve overall survival. Recent reports in the literature have suggested a dose-dependent risk of cardiovascular disease following radiation treatment for breast cancer. This article highlights new advances in radiotherapy for breast cancer that may help minimize radiotherapy doses to the heart.